Severe Preeclampsia, Antiphospholipid Syndrome, and Ulnar Artery Thrombosis in a Teenage Pregnancy: A Rare Association - M. Patabendige; G. Barnasuriya; I. Mampitiya (Case Reports in Obstetrics and Gynecology)
Antiphospholipid syndrome (APS) is associated with vascular thrombosis and pregnancy complications. It causes recurrent miscarriage and it is associated with other adverse pregnancy outcomes such as preterm delivery, intrauterine growth restriction, preeclampsia, and HELLP syndrome. Obstetric morbidity is one of the major manifestations of APS with a wide variety of clinical manifestations. This case describes a case of a severe preeclampsia in a 16-year-old primigravida at 29 weeks resulting in a caesarean delivery and subsequent finding of an ulnar artery thrombosis in postpartum period. APS was diagnosed on further investigations of her symptoms and signs.